2004
DOI: 10.3390/90400204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some New 4,5-Substituted-4H-1,2,4-triazole-3-thiol Derivatives

Abstract: In this study appropriate hydrazide compounds, furan-2-carboxylic acid hydrazide (1) and phenylacetic acid hydrazide (2) were converted into 1,4-substituted thiosemicarbazides 4a-e and 5a-e and 4-amino-5-(furan-2-yl or benzyl)-4H-1,2,4-triazole-3-thiols 7 and 10. The 1,4-substituted thiosemicarbazides were then converted into 5-(furan-2-yl or benzyl)-4-(aryl)-4H-1,2,4-triazole-3-thiols 8a-e and 9a-e. In addition, the azomethines 11a-d and 12a-d were prepared from the corresponding arylaldehydes and the 4-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…4 H -4-amino-3-mercapto-5-benzyl-1,2,4-triazole was prepared and characterized in our laboratory, according to literature [21]. Reduced-pressure evaporation of solvents was realized using a Büchi rotary evaporator R-200 (Büchi, Zurich, Switzerland) equipped with a Büchi heating bath B-490 and coupled to a Rotavac vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 H -4-amino-3-mercapto-5-benzyl-1,2,4-triazole was prepared and characterized in our laboratory, according to literature [21]. Reduced-pressure evaporation of solvents was realized using a Büchi rotary evaporator R-200 (Büchi, Zurich, Switzerland) equipped with a Büchi heating bath B-490 and coupled to a Rotavac vacuum pump.…”
Section: Methodsmentioning
confidence: 99%
“…Recent literature data mentions the synthesis of 4 H -4-amino-5-benzyl-3-mercapto-1,2,4-triazole as a potential antibacterial and antifungal compound [21], by the reaction of potassium 3-phenylacetyl-dithiocarbazate with hydrazine hydrate under reflux.…”
Section: Introductionmentioning
confidence: 99%
“…(3a)= C 6 H 5 (3b)= 2'Cl-C 6 H 4 (3c)= 3'Cl-C 6 H 4 (3d)= 4'Cl-C 6 H 4 (3e)= 4'F-C 6 H 4 (3f )= 2'OH-C 6 H 4 (3g)= 3'OH-C 6 H 4 (3h)= 4'OH-C 6 H 4 (3i)= 4'OCH 3 -C 6 H 4 (3j)= 2'NO 2 -C 6 H 4 (3k)= 3'NO 2 -C 6 H 4 (3l)= 4'NO 2 -C 6 H 4 (3m)= 3'OCH 3 , 4'OCH 3 -C 6 H 3 (3n)= 3'OCH 3 , 4'OH-C 6 H 3 (3o)= 3'OCH 2 CH 3 , 4'OH-C 6 H 3 (3p)= 4'N(CH 3 ) 2 -C 6 H 4 (3q)= 3'OCH 3 , 4'OCH 3 , 5'OCH 3 -C 6 H 2 (3r)= 3'OCH 3 , 4'OH, 5'OCH 3 -C 6 …”
Section: Toxtree Analysismentioning
confidence: 99%
“…Triazole and their analogues, considered as bioisosteres of imadazole [2], belongs to the most rapidly expanding group as fungicides [3][4][5][6][7][8]. They have well-known inhibitiory effects on the cytochrome P450-dependent lanosterol 14a-demethylase (CYP51) which affects the sterol biosynthesis of fungal cell membranes [8].…”
Section: Introductionmentioning
confidence: 99%
“…11 It is interesting to use 1,2,4-triazole derivatives as precusors in the synthesis of some important biologically active heterocycles, [12][13][14][15] which constitute an important class of organic compounds with diverse biological activities, including antiparasitic, analgesic, antibacterial and anti-inflammatory activities. [16][17][18][19][20][21] In addition, it was reported that triazole fused with a six-membered ring system is also found to possess diverse applications in the field of medicine. [22][23][24][25] The commonly known systems are triazolo-pyridines, 26 triazolo-pyridazines, 27 triazolo-pyrimidines, 28 triazolo-triazines, 29 triazolo-pyrazines, 30 triazolo-triazenes, 31 a few monomeric triazolo-thiadiazine, 31 and triazolo-thiadiazepines, 32 although there are not many triazoles fused to thiadiazines and thiadiazepines, there is a number of them that are incorporated into a wide variety of therapeutically important compounds possessing a broad spectrum of biological activities.…”
Section: Introductionmentioning
confidence: 99%